(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Insurance companies are in the business of taking risks of various kinds. All over the world, the insurance companies write the policies that deal with specific risks, and in many cases even underwrite exotic risks. As a direct corollary, therefore insurance companies should be good at managing their own risks. However the reality is little far from that. While these companies are good at assessing insurance risks for its policy holders, but not very good at setting up structures internally for managing their own operating and business risks. Over the past years Unit Linked Insurance Plans (ULIP) had emerged as a major player in savings mobilization. Investors had showed keen interest by subscribing to ULIP schemes anticipating higher returns. However with the global recessionary trend the performance of ULIP had been drastically affected. The BSE Sensex which had shot up to 21000 points came crashing down and stood at 8335 points on12th March 2009 and had greatly affected the Net Asset Value (NAV) across all the plans of various companies.This research paper elaborates the concept and proceeds to explain risk identification, distinguishes risk management in life insurance Unit Linked insurance Plans and details the risk management process. It also explains the risk management system and structure within the organization as per the IRDA Guidelines. Finally it forays on the vital issues and strategies relevant to the insurer, the policy holder and the IRDA as regulatory authority.